Formulation and evaluation of effervescent josaphine pineapple tablets - Mohd Rosdan, Faridatul Ain (2014)
There is an increasing demand in commercialization of native fruits for utilization as functional foods and medicinal extracts. Josapine pineapple is used in this study since it is a delicious and popular fruit due to its good aroma, flavour, juiciness, sweetness and texture. This study is mainly undertaken to design and optimize an effervescent tablet formulation of the Josapine pineapple by using the D-optimal experimental design methodology. This thesis is presented in two major parts namely, an evaluation of physicochemical properties of Josapine pineapple pulp and freeze-dried powder using Principal Component Analysis (PCA) and the optimization of an effervescent pineapple tablet formulation by using mixture design. At the beginning of this study, the physicochemical properties of Josapine pineapple pulp and freeze-dried powder were investigated because an understanding on the physicochemical properties between Josapine pineapple pulp and freeze-dried powder provides valuable information in order to develop an effervescent tablet formulation. PCA was then used to analyze the variations of physicochemical and sensory properties of the Josapine pineapple under different treatments (pure, 10 % or 20 % maltodextrin and 10 % or 20 % sugar) under two different conditions (pulp and freeze-dried powder). Josapine pineapple powder, citric acid, sodium carbonate and stevia were used in the formulations as independent variables. Tablets were prepared by direct compression method and evaluated for their disintegration time and sensory properties which were regarded as responses in a D-optimal design. From this study, it was found that freeze-dried pineapple powder with addition of maltodextrin and sugar can be differentiated based on physicochemical properties data and analysis. The optimum formulation contained pineapple powder, citric acid, sodium carbonate and stevia at 49.59 %, 20 %, 11.96 % and 18.45 %, respectively. In addition, optimum formulation has a very fast disintegration time and quite high overall acceptability which represents the consumer approval. The observed values of the responses obtained from the optimized formulation were very close to the predicted values where the Euclidean distance calculated for optimum formulation was equal to 0.26. This study reveals that the effervescent pineapple tablet has a wide potential for future development and can be enhanced for commercialization. This work may contribute towards Malaysia’s economic growth especially in the food and beverage industry.